NOVEL CORONAVIRUS (2019-nCoV): DISEASE BRIEFINGS - AL-TAMEEMI, KANAAN; KABAKLI, RAIAAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Coronavirus (CoV) (2019‐nCoV) is a large, enveloped, positive-sense, single-stranded RNA virus. The abnormal outbreak of 2019‐nCoV in Wuhan warns of the risk of CoV (2019‐nCoV) to public health which causes viral pneumonia outbreak. In our review, we will discuss the biology of CoVs and the potential risk of the novel CoV (2019‐nCoV) and guide us to strategic objectives for controlling the virus.